Evaluation of C-reactive protein as predictor of adverse prognosis in acute myocardial infarction after percutaneous coronary intervention: A systematic review and meta-analysis from 18,715 individuals - Liu, Shijie; Jiang, Hongcheng; Dhuromsingh, Menaka; Dai, Lei; Jiang, Yue; Zeng, Hesong (Frontiers in Cardiovascular Medicine, 2022)
Background: The outcome of patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) differs tremendously. Thus, proper prognostic biomarker is of great importance for clinical decision making. Methods: To study the relationship between the C-reactive protein and the prognosis of AMI patients undergoing PCI, the PubMed, EMBASE, Medline were searched from their inception to December 2021. Results: A total of 24 studies were eventually eligible into this meta-analysis, including 18,715 individuals. Our finding showed that elevated CRP had a statistically significant superiority in predicting all-cause mortality (OR: 3.22, 95% CI: [2.71, 3.84], p<0.00001), cardiovascular death (OR: 3.26, 95% CI: [2.30, 4.61], p<0.00001), major adverse cardiovascular events (MACEs) (OR: 2.85, 95% CI [2.08, 3.90], p<0.00001), heart failure (OR: 2.29, 95% CI: [1.48, 3.54], p=0.0002), recurrent myocardial infarction (OR: 1.76, 95% CI: [1.28, 2.43], p<0.001) and restenosis (OR: 1.71, 95% CI: [1.18, 2.47], p=0.004). Conclusion: Our meta-analysis suggests that CRP is a prospective predictor of the prognosis in patients with AMI undergoing PCI.